Nursing Students' Perceptions of New Health Law on Prior Learning Introduction Programs - Intening, Vivi Retno; Fitri, Narti (Health Access Journal, 2024)
Law Number 17 of 2023 has many pros and cons: prone to lawsuits, STRs that are afraid of being misused, and foreign health workers are allowed to work in Indonesia. The aim of this study was to know the perceptions of RPL STIKES Bethesda Yakkum Yogyakarta students about the issuance of Law Number 17 of 2023. Quantitative descriptive research design, population of 94 respondents with total population technique. The research instrument used a questionnaire. Univariate data analysis with a percentage formula. Characteristics of respondents based on the most age 26-35 years as many as 56 respondents (59.6%), the most female gender as many as 71 respondents (75.5%), and the most length of work 11-20 years as many as 55 respondents (58.5%). The perception category of RPL students mostly has a positive perception, as many as 93 respondents (98.9%). RPL students' perceptions of Law Number 17 of 2023 are in the positive category.